Unraveling the Mystery of Cold Stress-Induced Myocardial Injury - Kong, Xue; Liu, Haitao; He, Xiaole; Sun, Yang; Ge, Wei (Frontiers in Physiology, 2020)
Exposure to low ambient temperature imposes great challenge to human health. Epidemiological evidence has noted significantly elevated emergency admission and mortality rate in cold climate in many regions, in particular, adverse events in cardiovascular system. Cold stress is becoming one of the important risk factors for cardiovascular death. Through recent advance in echocardiography and myocardial histological techniques, both clinical and experimental experiments have unveiled that cold stress triggers a variety of pathological and pathophysiological injuries, including ventricular wall thickening, cardiac hypertrophy, elevated blood pressure, decreased cardiac function, and myocardial interstitial fibrosis. In order to examine the potential mechanism of action behind cold stress-induced cardiovascular anomalies, ample biochemical and molecular biological experiments have been conducted to denote a role for mitochondrial injury, intracellular Ca2+ dysregulation, generation of reactive oxygen species (ROS) and other superoxide, altered gene and protein profiles for apoptosis and autophagy, and increased adrenergic receptor sensitivity in cold stress-induced cardiovascular anomalies. These findings suggest that cold stress may damage the myocardium through mitochondrial injury, apoptosis, autophagy, metabolism, oxidative stress, and neuroendocrine pathways. Although the precise nature remains elusive for cold stress-induced cardiovascular dysfunction, endothelin (ET-A) receptor, endoplasmic reticulum (ER) stress, transient receptor potential vanilloid, mitochondrial-related protein including NRFs and UCP-2, ROS, Nrf2-Keap1 signaling pathway, Bcl-2/Bax, and lipoprotein lipase (LPL) signaling may all play a pivotal role. For myocardial injury evoked by cold stress, more comprehensive and in-depth mechanisms are warranted to better define the potential therapeutic options for cold stress-associated cardiovascular diseases.